Analisis Kinerja Keuangan PT GoTo Gojek Tokopedia Tbk Berdasarkan Net Profit Margin, ROA, dan ROE Periode 2019–2023 - Cut Risma Fandira; Zuraidah Zuraidah; Rusnaidi Rusnaidi (Jurnal Ekonomi Manajemen Akuntansi, 2026)
Financial performance is an important indicator for assessing the sustainability and growth prospects of a company, where a sustained negative net profit may indicate financial and operational problems (Aminah, 2015). The purpose of this study is to analyze the financial performance of PT GoTo Gojek Tokopedia Tbk for the period 2019-2023 based on NPM, ROA, and ROE. The research method used in this study is a qualitative method with a descriptive analysis approach. The data was sourced from the official website of PT GoTo Gojek Tokopedia Tbk for the period 2019-2023. The results show that all profitability ratios, namely Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE), are in an unfavorable condition and far below the standards set by Bank Indonesia (2004), namely NPM 3%–9.5%, ROA 0.5%–1.25%, and ROE 5%–12.5%. NPM was consistently negative from -276.74% (2019) to -373.12% (2023), indicating that the company has not been able to generate net income from its revenue due to high operating expenses. ROA was also negative throughout the period, ranging from -112.57% (2019) to -167.33% (2023), indicating that assets have not been utilized efficiently. Similarly, ROE recorded negative values from -162.02% (2019) to -253.41% (2023), reflecting that shareholders' capital has not been optimally managed and has not provided returns, so that overall financial performance requires a more effective financial management strategy.